DYNAMICS OF LOCAL ISLAM: FATWA OF MUHAMMAD BASIUNI IMRAN, THE GRAND IMAM OF SAMBAS, ON THE FRIDAY PRAYER ATTENDED BY FEWER THAN FORTY PEOPLE - Hamka Siregar (Al-Albab, 2013)
This article is an analitical work based on local Islam dynamic of Sambas society in the era of Sambas Sultanate. The work attempts to promote intellectual heritages such as the book of Cahaya Suluh, which could at least give us an idea that in a process of setting certain rules or istinbat, there is a need for flexibility. As can be observed from the whole argument built in this book, the process is completely flexible, not merely following one school of thought. As indicated in this paper, especially in the discussion of his thought, Muhammad Basiuni Imran used various references for his propositions. Although he was an advocate of the school of Syafi’i, he was still open to the other schools of thought. As a matter of fact, in the case of Friday prayer, his position was different from the school of thought he supported. He took that position because he considered the socio cultural conditions of Sambas at the time. Intellectual spirit shown by the Grand Imam of Sambas should continue to be emulated and expanded. It is a way to avoid the ‘blind’ taqlid against a certain school of thought, as such attitude can narrow human intelligence and reasoning which will eventually lead to collision with local reality that sometimes contains values that do not contradict with religion. In addition, the approach to the interpretation of law should look at its socio-cultural and historical background as this will keep the law strong and sustainable. In this way, Islam will be easily accepted without having to impose foreign culture on local people. Keywords: Dynamic, Islam, Sambas, Grand Imam, Muhammad Basuni Imran